EFEKTIVITAS POLA PEMBELAJARAN AGAMA HINDU DI SEKOLAH MENENGAH ATAS - Ni Komang Purni Marsini (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2021)
Hindu religious education as one of the subjects taught in schools ranging from primary, secondary, to tertiary education. This is an opportunity for Hindu religious education to shape the personality, mental attitude and character of students into suputra. But the reality is very different. The recognition of most students will be blurred in the values ​​of Hindu religious knowledge. The learning pattern of Hindu religious education is too theoretical, it does not touch the real life of students. Students spend their time understanding theory, but cannot deal with life's problems properly. As a result, Hindu Religious Education is trapped in memorization, not how to use Hinduism to solve life's problems. The rolling of the competency-based education paradigm, in response to the low level of relevance of educational outcomes, including Hindu religious education. This raises awareness of the need for a review, revitalization of Hindu Religious Education Learning Patterns in schools.This phenomenon encourages the author to conduct research on "The Effectiveness of Hindu Religion Learning Patterns in Senior High Schools. The purpose of this study is to analyze the effectiveness of Hinduism learning patterns in senior high schools.